2014
DOI: 10.1055/s-0033-1358931
|View full text |Cite
|
Sign up to set email alerts
|

Palliation of a malignant gastrocolic fistula with the use of an atrial septal defect occlusion device

Abstract: A 51-year-old Asian man with metastatic gastric adenocarcinoma presented with a 3-month history of profound diarrhea and weight loss. Laboratory evaluation was significant for anemia and hypokalemia. Computed tomography showed large tumor burden from the gastric antrum with invasion into the ascending colon. Esophagogastroduodenoscopy (EGD) revealed a gastrocolic fistula 30 mm in diameter within the posterior wall of the gastric antrum, extending for 6 cm and opening into the ascending colon (• " Fig. 1) along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…9 A few reported cases in the literature show successful treatment of a gastrocolic fistula using a cardiac septal defect closure device, direct clipping, colonic stent placement, or wire-guided simultaneous dual scope approach. [10][11][12][13] Our patient was successfully treated surgically and had an uneventful postoperative course after undergoing a robotassisted laparoscopic partial omentectomy, Billroth II gastrojejunostomy, Braun enteroenterostomy, and segmental transverse colectomy with side-to-side isoperistaltic anastomosis.…”
Section: Discussionmentioning
confidence: 94%
“…9 A few reported cases in the literature show successful treatment of a gastrocolic fistula using a cardiac septal defect closure device, direct clipping, colonic stent placement, or wire-guided simultaneous dual scope approach. [10][11][12][13] Our patient was successfully treated surgically and had an uneventful postoperative course after undergoing a robotassisted laparoscopic partial omentectomy, Billroth II gastrojejunostomy, Braun enteroenterostomy, and segmental transverse colectomy with side-to-side isoperistaltic anastomosis.…”
Section: Discussionmentioning
confidence: 94%
“…Perretta et al 40 demonstrated the efficacy of CSOs in the closure of gastrostomy defects in porcine models, showing a 100% success closure rate, without any adverse events. Malespin et al 41 used an ASD device to close a malignant gastrocolonic fistula with adjunctive therapy and duodenal stenting and reported successful closure after 6 weeks, suggesting that success was achieved because of the ASD device. The other seven studies were excluded because they did not use ASD or VSD AMPLATZER TM occluder devices.…”
Section: Discussionmentioning
confidence: 99%
“…A few novel methods have been described that do not involve surgery; to mention a few, in the case of Nici et al, dual endoscopic closure was achieved with use of Resolution clips [ 15 ]. Also in a case of large inoperable malignant gastrocolic fistula and gastric outlet obstruction, Malespin et al combined an Atrial Septal Defect closure device and a duodenal stent for palliation [ 16 ]. Though our patient's age was in the mid-80s, she was a good fit for surgical intervention and CT scan revealed clear boundaries for resection.…”
Section: Discussionmentioning
confidence: 99%